Constructing Fashion as an Educational Message: A Qualitative Single-Case Study of the Runway Program on Celebrities' TV - Aleisya Rafapela; Mirza Azkia Muhammad Adiba (Research Synergy Foundation, 2026)
Research on the construction of reality in television has predominantly focused on final broadcasts or audience reception, while the behind-the-scenes production process remains underexplored. This study presents a qualitative single-case study examining how educational messages about fashion are constructed within the Runway program on Celebrities TV, drawing on Berger and Luckmann's (1966) three dialectical stages: externalization, objectivation, and internalization. Data were collected through in-depth interviews with the creative team, producer, and six audience informants, six months of participant observation, and document analysis of five episodes; these three sources were triangulated to examine how message selection, production routines, and audience interpretation interrelate within this specific organizational context. The findings show that externalization occurs through subjective message selection, layered interview control, and informative-descriptive scriptwriting, while objectivation manifests through the simultaneous use of visuals, voice-over, and designer interviews. Within this case, two context-specific interpretive patterns emerged: objectivation consistency, wherein procedurally consistent construction across episodes was received differently depending on audience media literacy, and stratified internalization, wherein general audiences accepted the broadcast reality as given, fashion design students developed technical and identity-related appreciation, and industry practitioners additionally detected implicit promotional layers. These patterns are presented as illustrative observations from this specific case rather than generalizable theoretical propositions. The study recommends that the production team develop written guidelines distinguishing 'educating' from 'promoting,' create interactive discussion spaces for audiences, and that future research adopt longitudinal and quantitative approaches to test whether similar patterns occur in other settings.